Hegemony, Discourse, and Power Relations in Intra-Campus Student Organizations in Mojok.Co’s Satirical Journalism - Murdianto Murdianto; Ahmad Kirom (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study examines hegemonic power relations within intra-campus student organizations in Indonesia by analyzing senior–junior interactions as represented in satirical journalistic content published by Mojok.co between January 2024 and August 2025. Using a qualitative library research design and content analysis, the study is theoretically grounded in Michel Foucault’s concept of power–knowledge relations and Antonio Gramsci’s theory of hegemony. The findings demonstrate that power operates predominantly through symbolic and discursive mechanisms rather than overt coercion, where seniority is constructed as a legitimate source of authority that enables seniors to define organizational norms and moral values such as loyalty, discipline, and obedience. These values are internalized by junior members through everyday discourse and organizational rituals, resulting in the normalization of hierarchical relations and the perception of domination as a form of consensus. The study concludes that intra-campus student organizations function not only as spaces for leadership development but also as arenas for the reproduction of hegemonic power, in which regeneration processes tend to perpetuate inequality by reproducing existing senior–junior hierarchies rather than fostering critical and egalitarian organizational practices.